Cancer-specific SNPs originate from low-level heteroplasmic variants in human mitochondrial genomes of a matched cell line pair. (2nd January 2019) - Hedberg, Annica; Knutsen, Erik; Løvhaugen, Anne Silje; Jørgensen, Tor Erik; Perander, Maria; Johansen, Steinar D.
Abstract: Low-level mitochondrial heteroplasmy is a common phenomenon in both normal and cancer cells. Here, we investigate the link between low-level heteroplasmy and mitogenome mutations in a human breast cancer matched cell line by high-throughput sequencing. We identified 23 heteroplasmic sites, of which 15 were common between normal cells (Hs578Bst) and cancer cells (Hs578T). Most sites were clustered within the highly conserved Complex IV and ribosomal RNA genes. Two heteroplasmic variants in normal cells were found as fixed mutations in cancer cells. This indicates a positive selection of these variants in cancer cells. RNA-Seq analysis identified upregulated L-strand specific transcripts in cancer cells, which include three mitochondrial long non-coding RNA molecules. We hypothesize that this is due to two cancer cell-specific mutations in the control region.